All-terrain mobile robot desinfectant sprayer to decrease the spread of COVID-19 in open area - Prisma Megantoro; Herlambang Setiadi; Brahmantya Aji Pramudita (International Journal of Electrical and Computer Engineering (IJECE), 2021)
The application of disinfection is becoming popular in recent months due to the COVID-19. Usually, the disinfection is used by spraying the liquid into an object. However, the disinfection process for humans and objects in the human environment is still done manually and takes time and increases exposure to viruses. Robotic technology can be a solution to handle that problem. Following that problem, robot design is proposed with many abilities and features. The robot can operate in remote conditions and full function for approximately 56 minutes and spray the liquid for more than 1 meter. This research can effectively be applied in COVID-19 handlings.